Spark plasma sintering of TiC with TiAly as sintering aid: Mechanisms and microstructures - Alessandro Rizzi; María García-Fernández; Miguel Á. Rodríguez; Emanuele De Bona; Rodrigo Moreno; Mattia Biesuz (Open Ceramics, 2024)
TiC features an interesting combination of mechanical properties, high-temperature resistance, and lightness, making it an excellent candidate for several applications in harsh environments. However, its sintering to obtain bulk components is extremely challenging. Herein, we show that titanium aluminide is a promising sintering aid for TiC (5, 10, and 20 vol% were investigated). The aluminide allows the formation of a nearly fully dense component at 1350 °C by spark plasma sintering under 80 MPa. The aluminide forms a grain boundary secondary phase that promotes the Ti diffusion: Ti from TiC can be dissolved within the TiAly at the neck center and precipitate at the neck surface, while C can easily diffuse through the TiC lattice. Higher temperatures cause the extrusion of the aluminide out of the SPS die and its reaction with oxygen impurities. The final microstructure is constituted by nearly pure TiC with isolated alumina pockets at the triple points.